If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) = 2(x + 8) Reorder the terms: 4(-1 + x) = 2(x + 8) (-1 * 4 + x * 4) = 2(x + 8) (-4 + 4x) = 2(x + 8) Reorder the terms: -4 + 4x = 2(8 + x) -4 + 4x = (8 * 2 + x * 2) -4 + 4x = (16 + 2x) Solving -4 + 4x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 4x + -2x = 16 + 2x + -2x Combine like terms: 4x + -2x = 2x -4 + 2x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 2x = 16 + 0 -4 + 2x = 16 Add '4' to each side of the equation. -4 + 4 + 2x = 16 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = 16 + 4 2x = 16 + 4 Combine like terms: 16 + 4 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| 9(x+6)-48= | | 5c+6=26 | | m-531=-347 | | 7u=329 | | 8y+3=51 | | (v+7)(v-8)=0 | | -3x=-1(x-6) | | 4x^2-13x+20=4x+5 | | z-344=-245 | | (y-9)(y+3)=0 | | -2(-7n+6)-2(8n+1)=-22 | | f+50=97 | | 3(6-2x)=8x | | 5y^2-27y+10=0 | | 2x+3=34 | | -5g=-20 | | 4.8x+0.2(x-2)=3 | | x^2-16x+9=-4x-2 | | 4x-10=-2x+14 | | 15z^2+16z+4=0 | | 6x+10+14x=5(1+4x) | | 4x+4 -6x=8(x-2) | | 268=69-w | | -8n=80 | | 8x+4y+6=70 | | 2z+5=3z | | -10x+16=-2(5x-8) | | 2x(x+2)=3(x+2) | | 2x^3+9x^2-8x-36=0 | | 23-16=6x-2x+9x | | -6+3Y=3+2Y | | 12z^2-17z-5=0 |